Culture, economy, power : anthropology as critique, anthropology as praxis - Lem, Winnie; Leach, Belinda, 1954- (SUNY series in anthropological studies of contemporary issues., 2002)
"Grounded in a conviction that anthropological knowledge implies critique and that engaging in anthropology is also ultimately an act of praxis, various contributors explore the ways in which the precepts of Marxism continue to illuminate and enhance our understanding of culture, economy, and politics. They focus on the question of epistemology to examine the process of anthropological intellectual production in different national settings and analyze the ways in which hierarchies of power and forms of state domination figure in the formation of subjectivities in different ethnographic contexts. The authors also reflect upon how class, gender, ethnicity, racialized forms of ethnicity, as well as regional and national identities, are configured through the relationships involved in making a living under late capitalism."--Jacket